The Effect of Earnings Per Share (EPS) and Company Size on Company Value with Return on Assets as Moderating Variables (Case Study of Companies Registered on JII-70 during the Covid-19 Period in 2020-2021) - Fyna Maulina; Suryo Budi Santoso; Sri Wahyuni; Dwi Winarni (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study examines the effect of company size and Earnings Per Share (EPS) on firm value with Return on Assets (ROA) as a moderating variable in companies listed on JII-70 during the Covid-19 period 2020-2021. The sampling technique used in this study This is a purposive sampling technique so that as many as 98 data are obtained. The data analysis technique used is multiple regression analysis and Moderated Regression Analysis (MRA) with the help of the SPSS program. The results showed that the EPS variable had no effect on firm value, firm size had a negative effect on firm value, ROA strengthened the effect of the EPS relationship on firm value, and ROA weakened the effect of firm size on firm value.